The analysis of young people’s experiences of domestic violence: spiritual and emotional journeys through suffering - Collis, Sue M. (International journal of children's spirituality, 2009)
The hermeneutical analysis of the stories of young people who have experienced domestic violence is described as multi‐layered having been developed from a voice centred relational methodology. The purpose was to uncover the complexity of lived experience. As the analysis proceeded, the young people’s voices emerged as ‘feeling’ voices, encompassing emotionality. Each young person’s journey through suffering was characterised by individuality, but the analysis has offered a glimpse of commonality which is present within each of the young people’s stories. Their resilience, their journey from disempowering to humanising emotions and their indomitable spiritual powers have been revealed through the analytical process.